Blind Detection of Wideband Interference for Cognitive Radio Applications. (3rd September 2009) - Coulson Coulson, Alan J. Alan J.
Abstract : Cognitive radio technologies are being developed which allow heterogeneous systems to share spectrum access while minimizing interference to improve the overall efficiency of spectrum usage. Thus, one important function of a cognitive radio is dynamically to avoid transmitting in occupied spectrum by detecting signals received from unknown competing systems. Robust operation requires the detection of multiple wideband interferers of unknown statistics from a single received sample vector. This paper describes the hypothesis tests that must be evaluated to perform detection of such signals and discusses several methods for performing detection. Computer simulation results are presented to show that hidden Markov modelling and power spectral analysis with edge enhancement are more robust than a simple "interference temperature-" based energy detector.